2016
DOI: 10.18632/oncotarget.11545
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from a large-scale meta-analysis indicates eczema reduces the incidence of glioma

Abstract: We investigated the relationship between eczema and the risk of primary glioma. Relevant studies were selected through electronic searches of PubMed and EMBASE. A meta-analysis of 12 case-control studies and one cohort study was performed. A fixed effect model was applied to analyze 13 studies consisting of 10,897 glioma cases and 56,081 controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the strength of the associations. The data demonstrate that eczema significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Our results showed that patients with a history of eczema had a 0.69-fold lower risk of glioma than patients without eczema [1]. These findings revealed significant protective effects of allergic disease in terms of susceptibility to cancer.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our results showed that patients with a history of eczema had a 0.69-fold lower risk of glioma than patients without eczema [1]. These findings revealed significant protective effects of allergic disease in terms of susceptibility to cancer.…”
Section: Introductionsupporting
confidence: 55%
“…A case-control study involving 3812 subjects in Canada based on a questionnaire interview found a significant inverse association between eczema and stomach cancer (OR, 0.27; 95% CI, 0.10-0.90) and lung cancer (OR, 0.34; 95% CI, 0.20-wa0.70) [3]. Our previous study revealed an inverse relation between eczema and the risk of glioma (OR, 0.69, 95% CI, 0.61-0.78), suggesting that eczema may modify the risk of glioma by modulating the immune system [1]. A populationbased case-control study conducted in the United States by Wen et al reported that eczema had a significant protective effect against acute lymphoblastic leukemia among children (OR, 0.70, 95% CI, 0.50-0.90) [4].…”
Section: Epidemiological Studies Of Eczema and The Risk Of Cancermentioning
confidence: 90%
“…Investigating the relationship between AE and primary glioma in 13 observational studies (10 897 glioma cases and 56 081 controls), Wang et al . concluded that AE is associated with a significantly reduced risk of glioma (OR = 0.69, 95% CI 0.61–0.78).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Observational studies suggest that allergies (asthma, eczema, hay fever) are associated with lower glioma risk ( Wigertz et al, 2007 ; Berg-Beckhoff et al, 2009 ; Amirian et al, 2016 ; Wang et al, 2016 ) and, consistent with this, asthma-susceptibility genotypes are associated with a reduced risk of glioma ( Schwartzbaum et al, 2005 ). Short term use of anti-inflammatory medicine has also been reported to reduce glioma risk ( Scheurer et al, 2011 ); although other studies have found conflicting results ( Daugherty et al, 2011 ; Gaist et al, 2013 ).…”
Section: Risk Factors For Gliomamentioning
confidence: 69%